2023
DOI: 10.1177/17562864231207755
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and adverse effects of cannabidiol in adjuvant treatment of drug-resistant epilepsy: a systematic review and meta-analysis

Shengyi Liu,
Zihua He,
Jinmei Li

Abstract: Background: Epilepsy is one of the most common chronic brain diseases. Almost one-third of patients have drug-resistant epilepsy (DRE). Cannabidiol is being considered as a potential novel drug for treating DRE. Objectives: To investigate long-term efficacy and safety of cannabidiol in treatment of DRE and the differences in cannabidiol treatment among patients with different characteristics. Design: Systematic review and meta-analysis. Data sources and methods: Medline, Embase, and CENTRAL were searched for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Oral CBD trials conducted for a period of 3 months found mild side effects such as reduced appetite, weight gain/loss, and tiredness when prescribed at doses less than 10 mg/kg/day. However, higher doses (10–20 mg/kg/d) were associated with a higher rate of serious adverse events, including elevated liver transaminase and respiratory infections [ 61 63 ]. However, it is crucial to differentiate the effects based on the method of CBD application.…”
Section: Introductionmentioning
confidence: 99%
“…Oral CBD trials conducted for a period of 3 months found mild side effects such as reduced appetite, weight gain/loss, and tiredness when prescribed at doses less than 10 mg/kg/day. However, higher doses (10–20 mg/kg/d) were associated with a higher rate of serious adverse events, including elevated liver transaminase and respiratory infections [ 61 63 ]. However, it is crucial to differentiate the effects based on the method of CBD application.…”
Section: Introductionmentioning
confidence: 99%